PDA-CAD method for the determination of magnesium, pyridoxine and thiamine in a dietary supplement supported by analytical quality by design methodology - Rmandić, Milena; Radjenović, Miloš; Stanković, Jovana; Protić, Ana; Otašević, Biljana; Malenović, Andjelija (Archives of Pharmacy, 2021)
In this research, Analytical Quality by Design (AQbD) methodology was used to develop the HILIC-PDA-CAD method for the determination of magnesium, pyridoxine and thiamine content in a dietary supplement. Experiments were conducted on the Dionex Ulitimate 3000 HPLC system with PDA and CAD detectors. Separations were performed on the ZIC-HILIC PEEK column (100 × 4.6 mm, 5 μm) with a mixture of acetonitrile, acetone and ammonium acetate/ammonium formate aqueous solution (48:12:40, v/v/v) as the mobile phase. The detection was performed at 220 nm. The optimal settings of CAD were defined with the one-factor-at-a-time approach: evaporation temperature 50°C, filter constant 10 s, pressure gas 60 psi. The influence of qualitative (salt type) and quantitative factors (pH and salt concentration) on the magnesium retention factor, kMg and the selectivity factor between pyridoxine and chloride anion, αB6/Cl-, was tested using the I-optimal design. The design space was defined by Monte Carlo simulations and model coefficients’ errors were propagated with the aim of identifying the conditions that meet the following criteria: kMg3.5, with the probability π=95%. From the derived 2D-Design Space graph, 95 mM of ammonium formate pH 4.4 was selected as the optimal composition of the aqueous phase. The method was validated and its reliability in routine application was confirmed.
Keywords: HILIC-PDA-CAD; magnesium; pyridoxine; thiamine; AqbD